The effects of high-intensity interval training using “Tabata Protocol” on the physical fitness of teenage wrestlers - Elaheh Piralaiy; Saeid D. Nikoukheslat; Kawan saeidy (Sport Sciences and Health Research)
Background: The physical fitness is essential for wrestlers to perform successfully. The Tabata Protocol can be appropriate to develop these physical qualities.Aim: This study aims to investigate the effects of high-intensity interval training using “Tabata  protocol” on the physical fitness of teenage wrestlers.Material and Methods: 16 participants were randomly assigned to two groups of Tabata training (n=8) and the control group (n=8). All mentioned variables were measured before and after 4 weeks of the intervention. Tabata training group performed Tabata protocol in 2- 3 sets of 8 exercises with 20 sec of training and 10 sec of rest. The control group kept up their normal training routine during the same time. Physical fitness components were measured. The collected data were statistically analyzed by an independent t-test at a significance level of P>0.05.Results: Wrestlers in both groups significantly increased physical fitness components except flexibility (P<0.05). Tabata training was significantly more efficient in endurance of core muscle (P= 0.019, ES= 0.490) and upper body strength (P= 0.001, ES= 0.490) than control group (P<0.05). Also, results showed that for leg explosive power, only Tabata training had a positive effect (P= 0.026, ES=0.541).Conclusions: Our results suggest that wrestlers after Tabata protocol interventions can obtain better physical fitness, and event time benefits with more efficient performance and time-efficient manner compared with control group.